Upper mantle anisotropy and deformation beneath the major thrust-and-fold belts of Zagros and Alborz and the Iranian Plateau. Issue 3 (14th June 2018) - Sadeghi-Bagherabadi, Amir; Sobouti, Farhad; Ghods, Abdolreza; Motaghi, Khalil; Talebian, Morteza; Chen, Ling; Jiang, Mingming; Ai, Yinshuang; He, Yumei
SUMMARY: We present new SKS splitting measurements obtained from a temporary seismic broad-band network in western Iran across the Arabia–Eurasia collision zone. The average delay time over the entire network was found to be 1.27 ± 0.27 s. In the Zagros where the lithosphere attains its greatest thickness, the fast-axes are predominantly subparallel to the trend of the mountain ranges, suggesting a lithospheric origin of the anisotropy caused by transpressional deformation. In contrast in the Alborz, the fast-axes become subparallel to the absolute plate motion vectors and we propose that anisotropy is mainly controlled by the direction of the asthenospheric flow field. The central Iran region shows a more complex pattern of anisotropy that could be the result of variable and small-scale deformation fields in the crust and the shallow sublithospheric mantle.